Island biogeography of mixed‐species bird flocks: A gregarious nuclear species influences island area effects - Ari Martínez; Liping Zhou; Xingfeng Si; Ping Ding; Eben Goodale (Journal of Biogeography, 2024)
Aim Island biogeography theory has been extended to include various species interactions, but has yet to consider intraguild mutualisms. We compare species‐area relationships for mixed‐species flocks to those for the entire bird community and determine how ‘nuclear’ species, those important to flock formation or cohesion, which often have functional traits such as intraspecific gregariousness, influence flock species richness. We hypothesized that mixed flocks would only form on large islands where nuclear species are present. On the subset of larger islands, we expected flock species richness to rise with island area, reflecting a larger pool of species. Location Thirty‐one islands of varying area in the reservoir system of Thousand Island Lake, China. Taxon The resident forest bird community and its subcomponent of flock participants. Similar to elsewhere in southern China, the primary nuclear species was Huet's Fulvetta ( Alcippe hueti ), which averaged 20 individuals per flock, and led the flocks when present. Methods Birds were surveyed in the winter of 2017 and the autumn of 2021. Results The probability for a flock to be present, and the species richness of birds per transect, increased with island area, but the species richness of flocks did not. Flocks with Huet's Fulvetta were only found on islands larger than 30 ha. Flocks on smaller islands formed around secondary nuclear species typical of northern Chinese flocks. Main Conclusion Gregariousness as a functional trait may make nuclear species more susceptible to disappearing in small fragments, leading to flock collapse. The extreme gregariousness of fulvettas may also act to increase competition in the flocks they lead and limit the flocks' species richness. We encourage further comparisons of the species‐area curves of mixed‐species flocks and whole bird communities to better understand the influence of flocks on community assembly and species diversity.